2020
DOI: 10.1111/ffe.13186
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of matrix cracking propagation in cross‐ply laminated composites subjected to three‐point bending load using concurrent multiscale model

Abstract: The purpose of the present study is to analyze fiber-matrix debonding and induced matrix cracking formation as two major micromechanical damage modes in cross-ply composite laminates using a two-dimensional numerical approach. To this aim, the cross-ply laminates containing 90-degree layers are modeled, where the fibers are arranged randomly in transverse plies. Damage modes in this numerical model are simulated by the cohesive surface method. The performed analyses reveal that in the laminates with 90-degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…The linear region of the diagram indicates the elastic behavior of the element when undergoes deformation. The linear response is stopped by the initiation of damage 41 Tn=f()δ. Furthermore, the fracture energy, G c , which is the area under the T–δ curve as shown in Figure 3A is given by Gc=0δ00.5emf()δitalicdδ. In this study, to simulate the fiber–matrix debonding, the constitutive bilinear function for Mode‐I fracture suggested by Scheider and Brocks 42 is employed: Tn={centerσmaxδnnormalΔnnormalΔnδnσmaxδnδ0.normalΔnδ0δn<normalΔnδ00.5em06.5emδ0<Δn, where δ n and δ 0 are displacements across the interface at the beginning and at the end of the separation and σ max is the corresponding stress to δ n .…”
Section: Numerical Model—computational Micromechanicsmentioning
confidence: 99%
“…The linear region of the diagram indicates the elastic behavior of the element when undergoes deformation. The linear response is stopped by the initiation of damage 41 Tn=f()δ. Furthermore, the fracture energy, G c , which is the area under the T–δ curve as shown in Figure 3A is given by Gc=0δ00.5emf()δitalicdδ. In this study, to simulate the fiber–matrix debonding, the constitutive bilinear function for Mode‐I fracture suggested by Scheider and Brocks 42 is employed: Tn={centerσmaxδnnormalΔnnormalΔnδnσmaxδnδ0.normalΔnδ0δn<normalΔnδ00.5em06.5emδ0<Δn, where δ n and δ 0 are displacements across the interface at the beginning and at the end of the separation and σ max is the corresponding stress to δ n .…”
Section: Numerical Model—computational Micromechanicsmentioning
confidence: 99%
“…The CAT model addresses unidirectional composites while a later article deals with 2D composites 17 . It has been observed that cracking in 2D composites often initiates in the transverse fiber tows rather than in flaws in the unreinforced regions of matrix 5,7,17,22,23 . Nevertheless, so little is actually known about the matrix at‐large in a real composite, treating the matrix with transverse tows as a single entity with a different and equally unknown distribution of flaws seems like a reasonable approach.…”
Section: Approachmentioning
confidence: 99%
“…Evans and Zok 20,21 provide a very good comprehensive treatment, and review of earlier work, of the behavior and modeling of CMC with particular attention to failure with a single dominant matrix crack. The initiation of cracking is often in fibers/tows that are loaded transversely, with initiation in the fiber coatings that are intentionally weak for the purpose of promoting crack deflection when the fibers are along the loading axis 7,17,22,23 . As noted, Curtin et al.…”
Section: Introductionmentioning
confidence: 99%
“…The cohesive zone method is divided into bilinear cohesive model, trilinear cohesive model, exponential cohesive model, and so on according to the different traction and separation relationship. Due to its concise characteristics, bilinear and trilinear models have been widely used on both monotonic [22][23][24] and cyclic loading 25,26 on two or three-dimensional analysis and embedded in some finite element programs and softwares. The exponential cohesive model, which can be expressed by a single expression and a continuous curve, is closer to the constitutive of the material.…”
Section: Introductionmentioning
confidence: 99%